A novel method to model effects of natural defect on roller bearing. (June 2018) - Liu, Yuwei; Zhu, Yongsheng; Yan, Ke; Wang, Fangzhe; Hong, Jun
Abstract: The assumption that the defects extend axially throughout rollers or raceways was widely adopted in previous studies, however, this is hardly the situation in natural defects. A contact model that considered the geometric feature of natural defect was developed to analyze effects of defect on roller-raceway contact. The contact stiffness expression for defected roller-raceway was derived by numerical fitting. The contact stiffness expression was introduced into the quasi-static model of roller bearing to model defected roller bearing. The contact load distribution and stiffness of roller bearing were simulated under different defect sizes and operating conditions. Results demonstrate that roller bearing was insensitive to natural defects and the prevailing fatigue criteria is not applicable to roller bearing. Highlights: A roller-raceway contact model was developed to investigate natural defect. Based on roller-raceway contact analysis, the contact stiffness expressions were derived by numerical fitting. The defected roller bearing was modeled by considering the change of contact stiffness.